Study of lung function test in association with laboratory findings of serum iron in patients with chronic obstructive pulmonary disease - Sunil Kumar Gothwal; Vikram Palsaniya; Harish Chandra Barjatiya; Ruchita Banseria; Piush Sharma; Pramod Kumar Goyal; Vasudeva Murthy Challakere Ramaswamy; Yogendra Singh; Gaurav Gupta (Clinical Epidemiology and Global Health, 2022)
Background: The current cross-sectional study analyses patients' plasma iron measurements and spirometry to determine the relationship between serum iron, percent transferrin saturation, serum ferritin, total iron-binding capacity (TIBC), and forced expiratory flow (FEF 25–75%), forced expiratory volume 1(FEV1)/Forced vital capacity (FVC), FVC, and FEV1. Methods: Spirometry measurements were assessed by comparing reference values based on age, height, sex, and race. Descriptive analysis of data included percentages, means, and standard deviations. Multivariate analyses were done using the Pearson correlation test and the multiple linear regression method. Results: According to the findings, the average age of those who participated in the study was 59.63 ± 10.32 years old. Serum iron concentrations were shown to be extremely significant and positively correlated with the percent anticipated values of FVC, FEV1/FVC FEV1, and FEF (25–75%). The total iron-binding capacity was extremely significant and linked strongly with the percent expected values of FVC, FEV1, FEF (25–75%), and FEV1/FVC. The percent transferrin saturation was extremely significant and linked positively with the percent anticipated values of FVC, FEV1, FEF (25–75%), and FEV1/FVC. Conclusion: Plasma iron levels were independently linked with both FEV1 and FEF (25–75%) percent predicted in the current investigation. Consequently, the blood iron concentration in COPD patients can be utilized as a biomarker for assessing disease severity because it is relatively simple and inexpensive.